IMMUNOLOGICAL TOLERANCE IN ORGAN TRANSPLANTATION - M. Sh. Khubutiya; V. A. Gulyaev; V. B. Khvatov; V. L. Lemenev; S. A. Kabanova; M. S. Novruzbekov; K. N. Lutsyk; O. D. Olisov; S. V. Zhuravel'; G. V. Bulava; D. Kh. Tsurova; N. V. Borovkova; et al. (Трансплантология (Москва), 2017)
Modeling of  immune tolerance will  eliminate the  need  for  taking medications to prevent rejection. This  review of available literature covers the immune mechanisms of allograft rejection and the ways of tolerance induction. The role of mesenchymal stem  cells and using them for tolerance development have been discussed. The authors also draw attention to the fact  that  blood transfusion from an organ donor  leads to a decreased  intensity of the immune response to donor cells in transplantation.